2011
DOI: 10.7763/ijmlc.2011.v1.5
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Toxicity Models using MultigeneSymbolic Regression and Multiple Objectives

Abstract: In this contribution a multi-objective genetic programming algorithm (MOGP) is used to perform symbolic regression. The genetic programming (GP) algorithm used is specifically designed to evolve mathematical models of predictor response data that are "multigene" in nature, i.e. linear combinations of low order non-linear transformations of the input variables. The MOGP algorithm simultaneously optimizes the dual (and competing) objectives of maximization of 'goodness-of-fit' to data and minimization of model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The high-level crossover allows the exchange of one or more genes with another selected individual subject to the G max constraint. If an exchange of genes results in any individual containing more genes than G max , the genes will be randomly selected and deleted until the individual contains G max genes [16][17][18][19].…”
Section: Multi-gene Symbolic Regressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high-level crossover allows the exchange of one or more genes with another selected individual subject to the G max constraint. If an exchange of genes results in any individual containing more genes than G max , the genes will be randomly selected and deleted until the individual contains G max genes [16][17][18][19].…”
Section: Multi-gene Symbolic Regressionmentioning
confidence: 99%
“…The algorithm attempts to maximize diversity by ensuring that no individuals contain duplicate genes. The genes are randomly chosen, and the vector of unknown coefficients d is estimated using least squares normal equation as follows [16][17][18][19]:…”
Section: Multi-gene Symbolic Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al studied the design of metal catalysts [15], numerous articles can be found for the design of drugs [5,[16][17][18], Perdomo et al designed and improved biodiesel fuel blends [3] and Kasat et al summarized the applications of genetic algorithms in polymer science including polymer design [2].…”
Section: Problem Formulationmentioning
confidence: 99%
“…The crossover Eqs. (16)(17) and mutation Eqs. (18)(19) operators are applied to create the next generation (with N members) [27].…”
Section: The Non-dominated Sorting Geneticmentioning
confidence: 99%